Kesiapan Finansial Petani Kelapa Sawit dalam Peremajaan Kebun (Replanting) (Studi Kasus di Desa Sukamulya, Kecamatan Singkup, Kabupaten Ketapang) - Sudarwati, Ayuk; Sudrajat, Jajat; Oktoriana, Shenny (Universitas Galuh, 2025)
The purpose of this study is to analyze the income of oil palm farming, as well as to analyze the level of economic ability of oil palm farmer households in replanting. The sample in this study was farmers taken from Sukamulya Village as many as 64 respondents. The data analysis method used is quantitative analyzed using Microsoft Excel. The results of the study show that oil palm farmers are economically able to finance oil palm replantation. However, 21 year-old oil palm farmers have not been able to meet the needs of their farmers until the crop produces with 54% economic capacity. This is because 24 year-old Swiss coconut farmers have a higher income outside of agriculture (Non-Farm), which is 49% compared to income from oil palm. Thus, it can be concluded that the income outside of agriculture of oil palm farmers is very helpful for farmers to meet household needs.